Photocatalytic Carbon Dioxide Reduction with Water to CO and CH4 over Bio-sludge Modified TiO2 Composite - Beenish Tahir; Muhammad Tahir; Abdulrahman Alraeesi; Naveen Kumar (Chemical Engineering Transactions)
Photocatalytic reduction of carbon dioxide (CO2) is a promising strategy for converting greenhouse gases into valuable fuels and chemicals, contributing to sustainable energy solutions and climate change mitigation. In a continuous flow photoreactor system, this work investigates the use of waste-bio-sludge (BS) supported TiO2 (BS/TiO2) composite for photocatalytic reduction of CO2 using water as the reducing agent. The bio-sludge acted as a cocatalyst, promoting efficient charge separation and transfer in addition to higher visible light absorbance. Using optimized BS/TiO2 composite, the highest CO and CH4 yield rates of 3.82 and 4.39 µmol g-1 h-1 at selectivity 46.50 and 53.50 % were achieved. When compared to pure TiO2, the composite BS/TiO2 was able to produce CH4 at a higher yield rate. This was caused by the effective separation of charge carriers. This work contributes to the growing body of research on sustainable photocatalytic technologies, emphasizing the importance of designing efficient and robust photocatalysts for practical applications in CO2 utilization and renewable energy production.